2020
DOI: 10.1038/s41598-020-75375-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Connexin36 near the C-terminus switches binding affinities for PDZ-domain and 14–3–3 proteins in vitro

Abstract: Connexin36 (Cx36) is the most abundant connexin in central nervous system neurons. It forms gap junction channels that act as electrical synapses. Similar to chemical synapses, Cx36-containing gap junctions undergo activity-dependent plasticity and complex regulation. Cx36 gap junctions represent multimolecular complexes and contain cytoskeletal, regulatory and scaffolding proteins, which regulate channel conductance, assembly and turnover. The amino acid sequence of mammalian Cx36 harbors a phosphorylation si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…PTPN13 consists of multiple of PDZ domains and functions as a tumor suppressor (32). We have previously shown that perch Cx35, which has an identical PBM to Cx36, bound to the second PDZ domain of PTPN13 in a micro array screen (33). Consistent with this finding, we observed extensive colocalization of transiently expressed Cx36 and endogenous PTPN13 at gap junctions in transfected HEK293T cells (Figure 4F).…”
Section: Resultsmentioning
confidence: 99%
“…PTPN13 consists of multiple of PDZ domains and functions as a tumor suppressor (32). We have previously shown that perch Cx35, which has an identical PBM to Cx36, bound to the second PDZ domain of PTPN13 in a micro array screen (33). Consistent with this finding, we observed extensive colocalization of transiently expressed Cx36 and endogenous PTPN13 at gap junctions in transfected HEK293T cells (Figure 4F).…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of Cx36 to local domains of Ca 2+ influx and activated CaMKII underlies activity-dependent strengthening of electrical synapses in IO neurons (Turecek et al, 2014; Welsh and Turecek, 2017). Recent work demonstrated that phosphorylation of the CaMKII consensus site within Cx36 also increases PDZ binding (Tetenborg et al, 2020). The combined evidence implicates a feed-forward process in which CaMKII activation simultaneously increases electrical synapse strength and stabilizes gap junction intercellular channels within the extended PSD via interactions involving Cx36, SHANK3, and NMDAR1.…”
Section: Discussionmentioning
confidence: 99%
“…To study the effects of the FZD2 viruses, we investigated stage 28 (E5.5, Table S4) and 38 (E12.5, Table S3) after performing overexpression of high titre (>2 x 10 8 ) FZD2 viruses at stage 15 (E2.5). The location of FZD2 viruses was only determined retrospectively on histological sections stained with a Group-associated antigens (GAG), an antibody that recognizes specific proteins in the RCAS virus or (Gignac et al, 2023; Gignac et al, 2019; Hosseini-Farahabadi et al, 2017; Geetha-Loganathan et al, 2014; Hosseini-Farahabadi et al, 2013; Chen et al, 2013; Kowalik and Hudspeth, 2011) antibody against the FLAG sequence (Gignac et al, 2023; Tetenborg et al, 2020) (Table S7).…”
Section: Methodsmentioning
confidence: 99%